An association between volumes of the cardiac chambers and troponin levels in individuals submitted to cardiac coronary computed tomography. Issue 10 (14th June 2017) - Rozenbaum, Zach; Arbel, Yaron; Granot, Yoav; Cohen, Dotan; Shmilovich, Haim; Ziv‐Baran, Tomer; Chorin, Ehud; Havakuk, Ofer; Cohen, Merav; Berliner, Shlomo; Topilsky, Yan; Aviram, Galit
Abstract: Background: Previous echocardiographic studies have revealed an association between enlarged cardiac chamber volumes and elevated troponin concentrations. An automatic 4‐chamber volumetric analysis tool was adopted to investigate this association in patients who underwent cardiac‐gated computed tomography angiography (CCTA). Hypothesis: We hypothesized that troponin concentration within the normal range correlates with cardiac chambers' volumes. Methods: Serum troponin was obtained from 157 ambulatory patients before undergoing CCTA for nonacute coronary artery evaluation. Volumes of the cardiac chambers and the left ventricular mass were automatically analyzed and indexed to body surface area. Patients with a troponin concentrations within the upper quartile (>0.007 ng/mL, n = 39) were compared to patients with a troponin concentrations within the 3 lower quartiles of troponin concentrations (≤0.007 ng/mL, n = 118). Results: None of the patients had a troponin concentration >0.05 ng/mL (the 99th percentile of the general population). There were no significant differences in baseline characteristics between the groups. There were significant correlations between troponin and ventricular volumes after adjustments for age and gender. In an analysis that included 107 patients without any known heart diseases, including those pathological findings in the current CCTA, there were significant correlations between troponin and the left and right ventricular volumes after adjustments for age, gender, and baseline characteristics (odds ratio [OR]: 1.08, 95% confidence interval [CI]: 1.03‐1.14, P = 0.002 and OR: 1.11, 95% CI: 1.04‐1.19, P = 0.002; respectively). Conclusions: Using the technology of automatic volumetric analysis in individuals undergoing CCTA, an association between larger right and left cardiac chambers and higher levels of troponin concentration was shown.